HUBUNGAN KAUSALITAS ANTARA NILAI TUKAR EFEKTIF RIIL RUPIAH DAN PENANAMAN MODAL ASING LANGSUNG DI INDONESIA PERIODE 2000 – 2015 - Dimas Andy Bugiswo; Ahmad Zafrullah TN.; Sugeng Hariadi (Perpustakaan Universitas Surabaya, 2018)
This study aims to examine the causality relationship between real effective exchange rate and foreign direct investment in Indonesia as the host country. This study uses a quantitative approach with Ordinary Least Square (OLS) and Vector Autoregressive (VAR) methods based on the monthly data of the total Foreign Direct Investment (FDI) in Indonesia and the Real Effective Exchange Rate (REER) of rupiah during January 2000 to December 2015 period. This study is a reference to the research that has been done before in various countries including Asian countries such as China. According to the results of the empirical test, the real effective exchange rate has a positive impact on the foreign direct investment and statistically significance, this shows that the appreciation of rupiah promotes FDI inflow into Indonesia. The empirical result also shows that there is a correlation between the two variable and the causality of both variables are significant. The author believes that this phenomenon might be possible because the relationship between the two variable is dependent on the motives and the expectation of the future earning by the investing firms.